(untitled) (Journal of Pathology of Nepal, 2023)
Background: Male infertility is on the rise globally. It contributes to about 40-50% of all infertility cases. Semen analysis forms the basic investigation for the assessment of male factors of infertility, but it has its pitfalls. Literature review has suggested newer parameters of semen analysis such as sperm quality, which can have a significant role in the outcome of pregnancy. This study aims to assess sperm DNA integrity and calculate the DNA fragmentation index, which is a measure of the quality of sperm, thereby highlighting the need for assessment of sperm quality along with sperm quantity. Materials and methods: 459 cases underwent routine semen analysis along with the DNA fragmentation index. Sperm quality was assessed using Modified Acidic Aniline blue staining. The statistical analysis was done using SPSS using a t-test and Chi-square test. Results: Advancing age did not affect all parameters. The DNA fragmentation index showed no effect on sperm count. Unpaired t-test correlation showed a negative correlation between DNA fragmentation index and sperm motility, viability, and morphology. Conclusions: This study highlights the need for increasing awareness about the male-factor of infertility with special reference to the quality along with the routine quantitative assessment of sperm. A conventional semen analysis along with a DNA fragmentation index assessment can help the clinician put forward the choice of artificial reproductive techniques for the couple and provide an accurate success rate of treatment.